HUBUNGAN DAYA LEDAK OTOT TUNGKAI TERHADAP KECEPATAN TENDANGAN SABIT PADA ATLET PUTRI PENCAK SILAT WALET PUTI PELALAWAN - Arnilisya, Arnilisya; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study was to determine whether there is a strong power effect on the speed of writing sickle at the athletes of girls pencak silat walet puti pelalawan. The types of research conducted is descriptive to know the main variables with other variables. The population in this study is the athlete of martial arts daughter walet puti pelalawan talking 12 people. The sample technique used is total sampling (saturated samples), where all the population is sampled. Thus the sample in this study is 12 people samples of female athletes pencak silat walet puti pelalawan. The instrument is a long jump without prefix. After that, the data were processed with statistics, to test the normality by the lilifors test at a significant level of α (0.05). Hypothesis in the proposed is the relationship of explosive muscle limb power to the speed of sickle kick at the athlete's daughter martial arts walet puti pelalawan. Based on the results of the analysis, there is an average of X 155.6 and Y 19.58 there is an average installation of 1.635 with r test count = 0.869> from r table = 1.602. Means r arithmetic> r table. Thus tedapat relation of explosive muscle limb power to the speed of sickle kick at the athletes of girls pencak silat swallow puti pelalawan. Keywords: Exploding Leg Muscle , crescent tip speed, Pencak silat